Point-of-care echocardiography and thoracic ultrasound in the management of critically ill patients with COVID-19 infection: Experience in three regional UK intensive care units. (May 2023) - Jordan, Helen; Preston, Hannah; Hall, David P; Gifford, Hugh; Gillies, Michael A
Introduction: Point-of-care ultrasound (POCUS) has an established role in the management of the critically ill. Information and experience of its use in those with COVID-19 disease is still evolving. We undertook a review of cardiac and thoracic ultrasound examinations in patients with COVID-19 on the intensive care unit (ICU). Our aim was to report key findings and their impact on patient management. Methods: A retrospective evaluation of critically ill patients with COVID-19 was undertaken in three adult ICUs, who received point-of-care cardiac and/or thoracic ultrasound during the 2019–2020 COVID-19 pandemic. We recorded baseline demographic data, principal findings, change in clinical management and outcome data. Results: A total of 55 transthoracic echocardiographic examinations scans were performed on 35 patients. 35/55 (64%) echocardiograms identified an abnormality, most commonly a dilated or impaired right ventricle (RV) and 39/55 (70%) scans resulted in a change in management. Nine patients (26%) were found to have pulmonary arterial thrombosis on CTPA or post-mortem. More than 50% of these patients showed evidence of right ventricular dilatation or impairment. Of the patients who were known to have pulmonary arterial thrombosis and died, 83% had evidence of right ventricular dilatation or impairment. 32 thoracic ultrasound scans were performed on 23 patients. Lung sliding and pleural thickening were present bilaterally in all studies. Multiple B-lines were present in all studies, and sub-pleural consolidation was present bilaterally in 72%. Conclusion: POCUS is able to provide useful and clinically relevant information in those critically ill with COVID-19 infection, resulting in change in management in a high proportion of patients. Common findings in this group are RV dysfunction, multiple B-lines and sub-pleural consolidation.